UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN PAITAN (Tithonia diversifolia A. Gray) TERHADAP MORTALITAS LARVA PENGGEREK TONGKOL JAGUNG Helicoverpa armigera Hubner - Sandi Syahputra; Rusli Rustam; Desita Salbiah (UIR Press, 2022)
Borer pest of corn cobs (Helicovepa armigera Hubner) is a major pest of corn. Pest control can be done using plant-based insecticides from paitan leaf extract (Tithonia diversifolia A. Gray). This study aims to obtain the best concentration of paitan leaf extract in controlling corn cob borer Helicoverpa armigera. The study was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, University of Riau. The research was carried out using a completely randomized design (CRD), consisting of 5 treatments and 4 replications. The treatments used were several concentrations of paitan leaf extract, namely 0 gl-1, 25 gl-1, 50 gl-1, 75 gl-1and 100 gl-1. Parameters observed were initial death, lethal time 50, lethal concentration (LC50 and LC95), daily mortality, and total mortality. data. Data were collected from daily mortality and then descriptively analyzed and displayed graphically. Data lethal concentration (LC50 and LC95) were analyzed probit using the POLO-PC program, while other data such as initial death, total mortality, and lethal time (LT50) were analyzed with analysis of variance. Data from the variance analysis with significant effect will be continued using the smallest significant difference (LSD) test at the 5% level. Results showed that the application of paitan leaf extract with a concentration of 100 gl-1 water was able to control H. armigera with mortality of 55.00%. The proper concentration to lead mortality of 50% of larvae H. armigera was 10.3% or equal to 103 gl-1 of water of paitan leaf extract. Meanwhile, the proper concentration to lead mortality of 95% of larvae population H. armigera was 44.7% or equivalent to 447 gl-1 water of paitan leaf extract.